CircPan3 Promotes the Ghrelin System and Chondrocyte Autophagy by Sponging miR-667-5p During Rat Osteoarthritis Pathogenesis - Zeng, Jing; Zhang, Zhenzhen; Liao, Qing; Lu, Qijin; Liu, Jiemei; Yuan, Lixia; Liu, Gang (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to investigate the potential roles of circRNAs in regulating osteoarthritis (OA)-related ghrelin synthesis, autophagy induction, and the relevant molecular mechanisms. Results showed that Col2a1, Acan, ghrelin, and autophagy-related markers expression were downregulated, while matrix metalloproteinase 13 (MMP13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) expressions increased in both IL-1β-induced rat chondrocytes and cartilage tissues of OA rats. A total of 130 circRNAs and 731 mRNAs were differentially expressed in IL-1β-induced rat chondrocytes. Among them, we found that circPan3 expression was significantly decreased in both cellular and animal OA models. CircPan3 directly targeted miR-667-5p. CircPan3 overexpression promoted Col2a1, Acan, ghrelin, beclin 1, and LC3-II expression but reduced MMP13 and ADAMTS5 expression in rat chondrocytes, whereas overexpression of miR-667-5p exhibited opposite effects on the above markers. Furthermore, we found that miR-667-5p bound directly to the 3’-UTR sequence of ghrelin gene. Moreover, the circPan3-induced alterations in chondrocytes were antagonized by miR-667-5p overexpression. Taken together, our findings demonstrate that circPan3 promotes ghrelin synthesis and chondrocyte autophagy via targeting miR-667-5p, protecting against OA injury. This study provided experimental evidence that circPan3/miR-667-5p/ghrelin axis might serve as targets of drug development for the treatment of OA.